Radiometric vs. agar proportion methods for assessing ethionamide resistance and its clinical effects in multidrug-resistant tuberculosis - (:unkn) unknown (INT UNION AGAINST TUBERCULOSIS LUNG DISEASE (I U A T L D), 2009)
SETTING: Three centres for the treatment of multidrug-resistant tuberculosis (MDR-TB) in Istanbul, Turkey: Heybeliada Centre for Chest Diseases and Thoracic Surgery, Sureyyapasa Centre for Chest Diseases and Thoracic Surgery and Yedikule Centre for Chest Diseases and Thoracic Surgery. OBJECTIVE: To evaluate the presence of ethionamide (ETH) resistance and its effect on time to sputum smear negativity in MDR-TB patients who had not previously received second-line anti-tuberculosis drugs. DESIGN: Drug susceptibility testing for isoniazid (INH), rifampicin (RMP), ethambutol, streptomycin and ETH was performed on 50 patients treated between August 2004 and May 2005. Indirect agar proportion and BACTEC methods were used to determine ETH susceptibility. RESULTS: Of the patients who were resistant to at least INH and RMP, 11 (22%) (three [27.3%] new and eight [72.7%] retreatment) were resistant to ETH with the BACTEC method. Of 18 new patients, three (16.6%) were ETH-resistant using the BACTEC method compared to 8/32 (25%) retreatment patients. The mean time to smear negativity was 75.2 days in ETH-resistant patients and 50 days in susceptible patients (P < 0.05). Both ETH-resistant and -susceptible groups were homogeneous for factors that may have a possible effect on time to conversion. CONCLUSION: Not only ETH resistance but also age and radiologically advanced disease adversely affected time to sputum conversion.
Keywords: multidrug-resistant tuberculosis; ethionamide; drug resistance; sputum; MYCOBACTERIUM-TUBERCULOSIS; SUSCEPTIBILITY; 2ND-LINE; STRAINS; DRUGS